Integrating dynamic systems materials into a mechanical engineering curriculum through innovative use of web-based acquisition and hands-on application and use of virtual graphical user interfaces: Part 4: Alternate approaches for teaching fourier series applications - Avitabile, Pete (Experimental techniques (Westport, Conn.), 2008)
(In many of the older FFT analyzers, there was a set of cryptic commands that must be used in combination with odd sequences of button pushes in order to perform simple operations-this caused a distraction to the actual understanding of the material that was required to be learned.) In order to circumvent some of the problems noticed with the structured lab "button-pushing exercise" (as student evaluations often commented), a separate MATLAB graphical user interfaces (GUI) was developed to explore the Fourier Series for representation of common signals. ACKNOWLEDGMENTS National Science Foundation (NSF) Engineering Education Division Some of the work presented herein was partially funded by the NSF Engineering Education Division Grant EEC-0314875 entitled "Multi-Semester Interwoven Project for Teaching Basic Core STEM Material Critical for Solving Dynamic Systems Problems."